Seasonal pastoral climate advisory for Ethiopia: MAM Season (Mar-May 2025) - Dessalegn, Olika; Gebre, Liyuneh; Mamo, Girma; Sisay,Tewodros; Tolcha, Abu; Edao, Chala; Doyo, Jaldessa; Tesfaye, Lidya; Alemayehu, Sintayehu; Workeneh, Sintayehu; Tegegne, Getachew; Terefe, Tadesse; et al. (2025)
The March to May (MAM) 2025 seasonal forecast for Ethiopia's pastoral regions anticipates below-normal rainfall across most southern, southeastern, and eastern areas, except for the southwest zones and western parts of Borana and Guji. March is expected to be particularly dry, compounding the impacts of the OND 2024 rainfall deficit. Although some rainfall recovery is likely in April and May for southern agro-pastoral zones, the Somali and Afar regions are projected to remain significantly dry, posing serious risks to pastoral activities and livelihoods. Poor pasture conditions are expected in Afar, Eastern Borana, South Omo, and Northeastern Somali, with moderate availability in southeastern Borana and parts of the Somali region. These conditions threaten livestock health, increase the risk of disease outbreaks, and complicate forage transportation. Heat stress is likely to be more severe in Afar and Somali regions than in Borana.